2019
DOI: 10.1038/s41598-019-39318-8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Windows of Susceptibility by Temporal Gene Analysis

Abstract: Increased understanding of developmental disorders of the brain has shown that genetic mutations, environmental toxins and biological insults typically act during developmental windows of susceptibility. Identifying these vulnerable periods is a necessary and vital step for safeguarding women and their fetuses against disease causing agents during pregnancy and for developing timely interventions and treatments for neurodevelopmental disorders. We analyzed developmental time-course gene expression data derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Expression data were derived from 6 adult brains of the AHBA. Gene expression studies reported a later window of susceptibility in SZ compared to ASD 55 . The 22q11.2 deletion may, therefore, be in part driven by later onset mechanisms, which could explain why its FC-signature correlates to the adult spatial expression patterns of so many genes.…”
Section: Discussionmentioning
confidence: 99%
“…Expression data were derived from 6 adult brains of the AHBA. Gene expression studies reported a later window of susceptibility in SZ compared to ASD 55 . The 22q11.2 deletion may, therefore, be in part driven by later onset mechanisms, which could explain why its FC-signature correlates to the adult spatial expression patterns of so many genes.…”
Section: Discussionmentioning
confidence: 99%
“…ENCORE’s framework also provides an amenable space for additional analytics techniques, such as weighted correlation network analysis [61], which may provide further information depth to ENCORE’s protein-protein interaction network. This amenability is emphasized by the fact that ENCORE is open-source and freely available, allowing for extensions on a variety of techniques and tools, such as the SWOT Clock for identifying windows of susceptibility [5]. These possible extensions also apply to different types of expression data, as well as different databases, such as KEGG and functional categories [38, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of the developing human brain to chemicals has been associated with a number of neurodevelopmental disorders, including epilepsy and schizophrenia. The timing of exposure (i.e., prenatal vs. postnatal) and the type of toxicant are two important factors that determine whether chemical exposure perturbs human brain development ( Kisby et al, 2013 ; Heyer and Meredith, 2017 ; Bennett et al, 2019 ; Grandjean et al, 2019 ). There is experimental support for chemical-induced subthreshold perturbation of nigrostriatal neurons during vulnerable stages of neurogenesis, neuronal development and neuronal migration that bears on the susceptibility to PD in adult life ( Barlow et al, 2007 ; Charlton, 2013 ; Schaefers and Teuchert-Noodt, 2016 ).…”
Section: Brain Development and Environmental Chemicalsmentioning
confidence: 99%